English for Economics: Analysis of English Needs on Economic Students in ASEAN Economic Community (AEC) - Dewi Surani; Nugrahini Kusumawati (Journal of English Language Studies, 2018)
ABSTRACTEnglish competence becomes very crucial to face global competition which includes competition of human resources, education, and economy, Quality improvement human resources became the key to successfully facing the free market in the era of ASEAN economic Community (AEC). English as a general course that must be followed by students should be able to meet the demands of competence; this is of course needs appropriate material especially for economic students so that students can understand material and economic terms. Such material is known as ESP or Englishf or Specific Purpose. This study aims to determine the problems faced by STIE Bina Bangsa Economic students in learning English, the needs of economic students related to English for Economics material, as well as the preparation of material into the syllabus of English Economy. This research uses qualitative research method of descriptive case study that is describes the problems and needs of students in learning English (English for Economics) which then interpreted in the form of a syllabus framework. Keywords:        ESP, Needs Analysis, ASEAN Economic Comunity (AEC).